Emerging Market Global Players: The Case of Brazil, China and South Africa - Henri Bezuidenhout (MDPI AG, 2021)
A remarkable proliferation in the number of non-financial emerging multinational enterprises (NFEMNEs) and their share in the aggregate outward foreign direct investment (OFDI), along with the complexity of their FDI activities, has been witnessed over the past decades. Consequently, considerable interest has been generated within and among countries regarding the implications of these relatively new significant emerging global players for a range of economic and policy issues. In order to understand the gaps in knowledge pertaining to their identities, activities and impacts, this article employs the results of our 2015 emerging markets global players (EMGP) reports to make logical and informed insinuations about the structure and profile of NFEMNEs originating from China, Brazil and South Africa, the largest emerging markets in Asia, Latin America and Africa. We also synthesise and compare the outcomes of the 2015 EMGP reports of these OFDI home countries. We find the existence of a pattern in the ranked top NFEMNEs, from each country, in terms of industry sectors, regionalism and national bias. Furthermore, we establish that the respective NFEMNEs participated in international markets to pursue larger markets, natural resources and strategic assets and were not crowded out of their domestic markets by inward FDI.